The role of the composite modifier in the stabilization of the soil base. (2021) - Romanenko, I.; Petrovnina, I.; Eduard, Pint; Romanenko, M.
Abstract: The conducted research assesses the effectiveness of using metallurgical production waste (gas cleaning dust, slags and slurries) as modifiers of the structure of the ground base of the road surface. Laboratory and field tests were conducted to determine the main strength characteristics of the stabilized soils. The tests used fine-ground slags, dust from gas cleaners of metallurgical production and fine-ground sand from local quarries. The slags were modified with both alkaline hardening activators and Portland cement. The results obtained in the studies were compared with the indicators of soils stabilized with Portland cement. Based on the results of the study, the recommended percentage of stabilizer is 23–30% of the soil mass. Experimentally, it was found that the optimal ratio of components in the slag-alkali binder hardening activator is 60% NaOH + 40% Na2 SiO3 (1:1), and when using lime and soda, 10% of the slag consumption. The optimal humidity of the slag-ground mixture for producing slag-ground with high physical and mechanical properties is 13–16% for sandy loams and 16–18% for loams. The strength of cinder samples of alkali-stabilized components exceeds the strength of cement-based materials by 37–66 %.